计算:[(x+y)(x-y)-(x-y)^2+2y(x-y)]/(-2y)
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/07 02:01:03
计算:[(x+y)(x-y)-(x-y)^2+2y(x-y)]/(-2y)计算:[(x+y)(x-y)-(x-y)^2+2y(x-y)]/(-2y)计算:[(x+y)(x-y)-(x-y)^2+2y(
计算:[(x+y)(x-y)-(x-y)^2+2y(x-y)]/(-2y)
计算:[(x+y)(x-y)-(x-y)^2+2y(x-y)]/(-2y)
计算:[(x+y)(x-y)-(x-y)^2+2y(x-y)]/(-2y)
原式=【(X-Y)(X+Y-X+Y)+2Y(X-Y)】/-2y
=【2y(x-y)+2y(x-y)】/-2y
=4y(x-y)/-2y
=-2(x-y)
=[x^2-y^2-(x^2-2xy+y^2)+2xy-2y^2]/(-2y)
=(x^2-y^2-x^2+2xy-y^2+2xy-2y^2)/(-2y)
=(4xy-4y^2)/(-2y)
=-2x+2y
[(x+y)(x-y)-(x-y)²+2y(x-y)]/(-2y)
=(x-y)[(x+y)-(x-y)+2y]/(-2y)
=(x-y)(x+y-x+y+2y)/(-2y)
=4y(x-y)/(-2y)
=-2(x-y)
=2y-2x
={(X-Y)[X+Y-(X-Y)+2Y]}/(-2Y)
=[4Y(X-Y)]/(-2Y)
=-2Y(X-Y)
=-2XY+2Y^2
这种题目不难,一步一步慢慢来就行了
原式=(x-y)[(x﹢y)-(x-y)﹢2y] ∕ (-2y)=(x-y)4y ∕ (-2y)=-2(x-y)=2y-2x
[(x+y)(x-y)-(x-y)^2+2y(x-y)]/(-2y)
=[x^2-y^2-(x^2-2xy+y^2)+2xy-2y^2]/(-2y)
=[4xy-4y^2]/(-2y)
=2y-2x
计算(-x-y)(y-x)+(-x-y)(x+y),
行列式计算 x y x+y y x+y x x+y x y|x y x+y ||y x+y x ||x+y x y |
计算 (x²/x+y)-x-y
计算:y-x分之x+y+x-y分之y-y-x分之2x-y
计算2/3x-2/x+y(x+y/3x-x-y)/x-y/x
计算:[(x+y)(x-y)-(x-y)^2+2y(x-y)]/(-2y)
计算(-x-y)²
计算:(x+3y)(2x-y)
计算:(2x-3y)(x+y)
计算:(x+2y)(2x-y)
计算:(-x-2y) * (3x-y)
计算:(x+y)-3(x-2y).
计算:(x-y+9)(x+y-9)
计算(x+y-z)(x-y-z)
计算:(x-y+z)(-x+y+z)
计算:-(x+y)+(x-y) 要求:
计算2x/x-y
计算 x(x-3y)